Self-Enforcing Trade : Developing Countries and WTO Dispute Settlement - Bown, Chad P. (Chad Philips), 1972- (Book collections on Project MUSE., 2009)
"Examines challenges and costs of developing countries accessing WTO dispute settlement process. Reviews WTO's extended litigation process, highlighting areas countries have to master--international economics, law, and politics. Assesses recent efforts to help countries overcome these hurdles and proposes a solution to largest obstacle: lack of information, monitoring, and surveillance"--Provided by publisher.